ISOLASI Bacillus thuringiensis BERL. DARI TANAH DAN PATOGENISITASNYA TERHADAP LARVA Crocidolomia binotalis ZELL. PADA TANAMAN SAWI (Brassica juncea L.) - Khaeruni, Andi; Rahayu, M; Purnamaningrum, Nenden Teja (Jurnal Agroteknos, 2012)
The aim of this research was to know the pathogenicity of B. thuringiensis against larvae of   C. binotalis Zell on Caisin Plant. The B. thuringiensis isolates were isolated using serial dilution technique, from soil samples that were taken from some locations in Southeast Sulawesi. Pathogenicity test on larvae III of C. binotalis was done using bioassay method. Mortality value was used to know the virulence level of  B. thuringiensis at 7 days after application. The result showed that there were 37 soil samples containing B. thuringiensis and the number of B. thuringiensis isolates were 65. isolates KU-ST7, MN-ST4, KNW-ST8, KLK- ST5,KLK-ST4 and KU-ST4 had the highest pathogenicity and virulence levels, because they had the highest efffect on C. binotalis larvae mortalities, i.e: 100%, with  LT50  value of 2-4  days after application. Key word : Bacillus thuringiensis Berl., bioassay test. Crocidolomia binotalis Zell.,